2001
DOI: 10.1097/00005537-200102000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Decalcification of Human Temporal Bones

Abstract: This study demonstrates that microwave decalcification provides an efficient and reliable means of processing human temporal bones for histological and histochemical examination. Decalcification time is significantly reduced with no apparent adverse effects on structural preservation or antigenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 12 publications
0
39
0
Order By: Relevance
“…Cunningham et al (2001) described an alternative for IHC of human temporal bones that used a decalcification method with a microwave oven process. A good signal-to-noise ratio of the immunostaining of Na + K + -ATPase in the human organ of Corti, as well as acceptable morphological preservation, was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Cunningham et al (2001) described an alternative for IHC of human temporal bones that used a decalcification method with a microwave oven process. A good signal-to-noise ratio of the immunostaining of Na + K + -ATPase in the human organ of Corti, as well as acceptable morphological preservation, was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the Sox10 expression data demonstrated the utility of our temporal bone preparation procedure [43], [71] and immunostaining assay using a frozen sectioning process to identify a particular transcription factor with low expression in human postmortem cochlear tissues. Further quantitative studies of lateral wall degeneration associated with candidate regulatory factors (identified from animal models) in human temporal bones will significantly advance our understanding of the causes of presbyacusis and other auditory disorders.…”
Section: Discussionmentioning
confidence: 82%
“…The fixative was perfused gently through the oval window using a blunt-tip, 16-gauge needle covered with appropriately sized tygon tubing. The perfused temporal bones were then immersed in fixative for 48–72 hours for frozen section preparation and 12–22 hours for paraffin section preparation followed by rinsing and decalcification using a microwave protocol as per our previous description [43]. The total time of decalcification was between 3–6 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…4,5,15 However, more recent findings show that microwaving significantly reduces decalcification time, with no obvious adverse effects on the structure and antigenicity. 2,7,10 Microwaving also reduces the time taken for fixation, dehydration, infiltration, clearing, and staining.…”
Section: Decalcificationmentioning
confidence: 99%